RETRACTED: Hepatoma Cell-Derived Extracellular Vesicles Promote Liver Cancer Metastasis by Inducing the Differentiation of Bone Marrow Stem Cells Through microRNA-181d-5p and the FAK/Src Pathway - Wei, Huamei; Wang, Jianchu; Xu, Zuoming; Li, Wenchuan; Wu, Xianjian; Zhuo, Chenyi; Lu, Yuan; Long, Xidai; Tang, Qianli; Pu, Jian (Frontiers in Cell and Developmental Biology, 2021)
Bone marrow mesenchymal stem cells (BMSCs) are beneficial to repair the damaged liver. Tumor-derived extracellular vesicles (EV) are notorious in tumor metastasis. But the mechanism underlying hepatoma cell-derived EVs in BMSCs and liver cancer remains unclear. We hypothesize that hepatoma cell-derived EVs compromise the effects of BMSCs on the metastasis of liver cancer. The differentially expressed microRNAs (miRNAs) were screened. HepG2 cells were transfected with miR-181d-5p mimic or inhibitor, and the EVs were isolated and incubated with BMSCs to evaluate the differentiation of BMSCs into fibroblasts. Hepatoma cells were cultured with BMSCs conditioned medium (CM) treated with HepG2-EVs to assess the malignant behaviors of hepatoma cells. The downstream genes and pathways of miR-181d-5p were analyzed and their involvement in the effect of EVs on BMSC differentiation was verified through functional rescue experiments. The nude mice were transplanted with BMSCs-CM or BMSCs-CM treated with HepG2-EVs, and then tumor growth and metastasis in vivo were assessed. HepG2-EVs promoted fibroblastic differentiation of BMSCs, and elevated levels of α-SMA, vimentin, and collagen in BMSCs. BMSCs-CM treated with HepG2-EVs stimulated the proliferation, migration, invasion and epithelial-mesenchymal-transition (EMT) of hepatoma cells. miR-181d-5p was the most upregulated in HepG2-EVs-treated BMSCs. miR-181d-5p targeted SOCS3 to activate the FAK/Src pathway and SOCS3 overexpression inactivated the FAK/Src pathway. Reduction of miR-181d-5p in HepG2-EVs or SOCS3 overexpression reduced the differentiation of BMSCs into fibroblasts, and compromised the promoting effect of HepG2-EVs-treated BMSCs-CM on hepatoma cells. In vivo, HepG2-EVs-treated BMSCs facilitated liver cancer growth and metastasis. In conclusion, HepG2-EVs promote the differentiation of BMSCs, and promote liver cancer metastasis through the delivery of miR-181d-5p and the SOCS3/FAK/Src pathway.